Imaging-guided nanomedicine development. (August 2021) - Bernal, Aurora; Calcagno, Claudia; Mulder, Willem J.M.; Pérez-Medina, Carlos
Summary: Nanomedicine research is an active field that produces thousands of studies every year. However, translation of nanotherapeutics to the clinic has yet to catch up with such a vast output. In recent years, the need to better understand nanomedicines' in vivo behavior has been identified as one of the major challenges for efficient clinical translation. In this context, noninvasive imaging offers attractive solutions to provide valuable information about nanomedicine biodistribution, pharmacokinetics, stability, or therapeutic efficacy. Here, we review the latest imaging approaches used in the development of therapeutic nanomedicines, discuss why these strategies bring added value along the translational pipeline, and give a perspective on future advances in the field.